Digitalization, Financial Development, and Institutional Quality on ASEAN Economic Growth - Najma Taralia Farah; Anton Bawono; Navi Risanti; Surya A. Fajar; Ali Samai Mata; Abd Fajeri Pita (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2026)
This study assesses the impact of digital transformation and advancements in the financial sector on economic growth in the ASEAN area, with institutional quality acting as a moderating variable. The methodology employed is dynamic panel data analysis utilizing the System-Generated Method of Moments (SYS-GMM) and Moderated Regression Analysis (MRA). The estimation results indicate that the impacts of digital transformation and financial development on economic growth are not consistently direct and significant. Nonetheless, institutional quality generally enhances this association, although the effect is not uniform across all sampled nations. The results demonstrate that the impacts of digitalization and the financial sector on growth are not consistently straightforward, but are significantly influenced by the efficacy of governance in each nation. This emphasizes that technology advancement must be paired with the enhancement of supporting institutions to facilitate optimal economic growth.